2014
DOI: 10.1088/1755-1315/18/1/012182
|View full text |Cite
|
Sign up to set email alerts
|

Validation of MODIS Data for Localized Spatio-Temporal Evapotranspiration Mapping

Abstract: Abstract. Advancement in satellite remote sensing sensors allow evapo-transpiration (ET) from land surfaces to be derived from selected reflectance and emmitance in visible and thermal infrared wavelengths, such as using Moderate Solution Imaging Spectrometer (MODIS). In this paper, we report the validation of recent MODIS-generated higher-order global terrestrial ET product 16A2. The main focus of this paper is to devise the follow-up calibration for the localised region covering the entire Malaysia peninsula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Because of the differences between the satellite-and ground-based rainfall data, calibration is essential to minimize existing errors over the study area [47]. Details of the calibration scheme were provided in Nadzri and Hashim [48] and therefore only a brief description is given here.…”
Section: Calibration For Evapotranspiration (Et) Retrieval From Modismentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the differences between the satellite-and ground-based rainfall data, calibration is essential to minimize existing errors over the study area [47]. Details of the calibration scheme were provided in Nadzri and Hashim [48] and therefore only a brief description is given here.…”
Section: Calibration For Evapotranspiration (Et) Retrieval From Modismentioning
confidence: 99%
“…The satellite-based ET provides data at global scales. Although several validations of those datasets have been done for other climates, such as America and Asia [49], specific validation, particularly for tropical regions was conducted by Nadzri and Hashim [48]. Those studies suggested that it is necessary to calibrate data to obtain better results.…”
Section: Calibration For Evapotranspiration (E T ) Retrieval From Modmentioning
confidence: 99%